The relationship between self-regulation, self-efficacy, and psychological well-being among Salahaddin University student in Kurdistan - Saleh, Reben Ramadhan (Kulliyah of Education, International Islamic University Malaysia, 2021)
Self-regulation, self-efficacy, and psychological well-being are essential requirements in the academic environment. Psychological well-being is an indispensable ingredient for students’ emotional balance and healthy development because a low level of psychological well-being modifies unsuccessfulness in educational settings. The recent study investigated the relationship between self-regulation, self-efficacy, and psychological well-being among Kurdish students at Salahaddin University. It holds the following objectives: (i) to examine the prevalence level of self-regulation, self-efficacy, and psychological well-being among Salahaddin undergraduate students; (ii) to examine the relationship of self-regulation and self-efficacy with psychological well-being among Salahaddin undergraduate students; and (iii) to examine the effect of self-regulation and self-efficacy on psychological well-being among Salahaddin undergraduate students. The used data comprised 407 students after removing outliers. The quota sampling technique was chosen in the present study. Analysis techniques were descriptive, person correlation, and Multiple Regression Analysis (MRA). The research shows that there is a low level of self-regulation and self-efficacy among Salahaddin undergraduate students. However, psychological well-being is high. The study further demonstrates a positive and statistically significant relationship between self-regulation, self-efficacy, and psychological well-being among Salahaddin undergraduate students. Finally, the study shows that only self-regulation has a significant effect on the psychological well-being of Salahaddin undergraduate students.